Zasób Archiwum Miejskiego w Bydgoszczy w latach 1909-1920 (Kronika Bydgoska, 2018)
The Municipal Archives in Bydgoszcz were founded on November 3, 1909. The purpose of this institution was protection of the archives and other cultural assets. In the beginning of the article, the author describes the history of the archives. It is followed by presentation of the archival resources based on the archive source in the form of Archiv-Katalog. The archives feature old-Polish records, documents regarding administration and finances of the city, reports documenting contemporary times, and museum objects.